Comparative study on intestinal microbiome composition and function in young and adult Hainan gibbons (Nomascus hainanus) - Li,Yimeng; Bi,Yu; Yang,Liangliang; Jin,Kun (PeerJ, 2022)
The Hainan gibbon is one of the most endangered primates in the world, with a small population size, narrow distribution range, and high inbreeding risk, which retains the risk of species extinction. To explore the composition and functional differences of the intestinal microbiome of Hainan gibbons at different ages, the faecal microbiomes of young and adult Hainan gibbons were analysed using metagenome sequencing. The results showed that the dominant phyla in the intestinal tract of young and adult Hainan gibbons were Firmicutes and Bacteroidetes, and the dominant genus was Prevotella. Linear discriminant analysis effect size analysis showed that Firmicutes, Ruminococcus, Clostridium, and Butyrivibrio were significantly more abundant in adults than in young, whereas Bacteroidetes, Proteobacteria, Prevotella, and Bacteroides were significantly more abundant in young than in adults. In terms of gene function, the adult Hainan gibbon intestinal microbiome generally harboured a higher abundance of genes related to metabolic processes, such as carbohydrate, amino acid, and nucleotide metabolism. This may be due to adaptive advantages for adult Hainan gibbons, such as stable and mature intestinal microbiome composition, which allows them to utilise diverse foods efficiently. In summary, this study helps understand the dynamic changes in the intestinal microbiome of young and adult Hainan gibbons and plays a key role in the health monitoring and rejuvenation of their population.
Keywords: Hainan gibbon (Nomascus hainanus); Intestinal microbiome; Metagenome